The renoprotective effect of oral Tadalafil pretreatment on ischemia/reperfusion injury in rats - Medeiros,Vanessa de Fátima Lima Paiva (2017)
Abstract Purpose: To evaluate the effect of tadalafil in renal ischemia/reperfusion (I/R) injury in rats Methods: Group I/R saline rats (n=6) were subjected to 45 minutes of left renal ischemia and treated with saline; the I/R tadalafil rats (n=6) received oral 10mg/kg tadalafil microemulsion one hour before ischemia. In both groups, 8 hours after ischemia, laboratory analysis were performed Results: Better tissue perfusion was lower in ischemic left/kidney than in right/kidney in saline group, suggesting reduced kidney clearance. Fluorescence in left/kidneys of tadalafil treated rats was lower than in right/kidneys (difference not significant). The fluorescence signal intensity in kidneys of tadafil treated rats was higher than in saline rats. TNF-α levels were significantly lower in I/R tadalafil group rats compared to I/R saline group (154±10.3 vs 391.3±12.3), as well as IL-1β (163.4±13.2 vs 279±11.5pg/dL), and IL-6 (122.9±8.1 vs 173.7±6.3 respectively; p=0.0001). Urea, creatinine and C-reactive protein were significantly lower in tadafil treated rats then in saline group Conclusion: Tadalafil therapy decreased the expression of circulating pro-inflammatory cytokines in a renal I/R rodent model, while improving kidney function proofs.